Uji Konsentrasi Plant Growth Promoting Rhizobacteria (PGPR) dalam Memacu Perkecambahan Biji Poliembrioni pada Biji Jeruk Siam Banjar - Sri Wahyuni; Noor Laili Aziza; Yusriadi Marsuni (Universitas Lambung Mangkurat, 2020)
Plant Growth Promoting Rhizobacteria (PGPR) or Rhizobacteria Plant Growth Boosters (RPPT) are non-pathogenic soil microbes found in plant roots that can increase plant growth and stimulate plant growth, PGPR's role in increasing growth and production, especially plant germination is the ability PGPR in synthesizing growth hormones and can provide protection against pathogens that attack plants so it is very good to be applied to a variety of plants. One of them is the banjar orange which is a typical fruit of South Kalimantan which has polyembryony seeds which are several embryos in one seed. Efforts in developing the productivity of banjar siam citrus cultivation are using PGPR. This study aims to determine the effect of the application of PGPR concentrations in spurring the germination of polyembryony seeds in banjar siam beans and to determine the best PGPR concentrations in stimulating the germination of polyembryony seeds in banjar siam seeds. This study uses a completely randomized design (CRD) consisting of a single factor with six replications and five treatments namely P0 (concentration without PGPR), P1 (PGPR concentration 15ml.1-1), P2 (PGPR concentration 30ml.1-1), P3 (PGPR concentration 45ml.1-1), and P4 (PGPR concentration 60ml.1-1). This research was conducted at the Production Laboratory and Integrated Laboratory of Agroecotechnology Department, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru. The research lasted for two months, starting from April to May 2019. The results showed that the application of PGPR concentrations had an effect on spurring the germination of polyembryony seeds on Banjar siam beans at the age of 7 days and 14 days, but the treatment had no effect on the germination of polyembryony seeds at the age of 21 HST, percentage of germination age 7 HST, 14 HST, and 21 HST, the speed of germination either normally or polyembryony, germination length, number of germination, and root length. The best concentration of PGPR in stimulating polyembryony germination in banjar siam seeds is in the control treatment or P0 (concentration without PGPR) at the age of 7 HST and 14 HST.